Peningkatan Literasi Teknologi melalui Sosialisasi Augmented Reality sebagai Media Pembelajaran Interaktif di SD Swasta Bintan Tanjungpinang Kota - Yos Ekaristi Manik, Agustina Sartika; Rada, Dwi Cahya; Fahmitra, Novrizal Fattah; Yusiani, Dwila Sempi; Dio, Rafi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The development of digital technology has had a significant impact on the world of education, particularly in creating more interactive and immersive learning media. One technology that has great potential in supporting the teaching and learning process is Augmented Reality (AR). This Community Service activity is carried out by the Faculty of Engineering and Maritime Technology (FTTK) of Raja Ali Haji Maritime University (UMRAH) at Bintan Private Elementary School in Tanjungpinang City, with the aim of introducing the concept and utilization of AR technology as interactive learning media to teachers and students. The activities include socialization, demonstrations of AR use, as well as discussion and evaluation sessions. The results of the activities show high enthusiasm from the participants, as well as an increased understanding of the use of AR in the context of learning, particularly in the field of shipping that requires the visualization of technical objects. Although there are limitations in infrastructure, this activity successfully encouraged initial initiatives in the integration of innovative technology in the school environment. This event also serves as a means to strengthen the role of UMRAH in supporting the development of local education based on technology